Guidelines for the management of emergencies and critical illness in pediatric and adult patients with sickle cell disease - Armand Mekontso Dessap; Stephane Dauger; Mehdi Khellaf; Maite Agbakou; Sophie Agut; François Angoulvant; Jean-Benoît Arlet; Cécile Aubron; Florent Baudin; Florence Boissier; Nicolas Bounaud; Pierre Catoire; et al. (Annals of Intensive Care)
Abstract Forty-two questions were evaluated concerning management of emergencies and critical illnesses in paediatric and adult patients with sickle cell disease. The assessment covered the following areas: patient referral, vaso-occlusive crisis, acute chest syndrome, transfusion therapy, and priapism. The patient referral category included guidelines for admission to intensive care unit and management at specialized reference centers. The vaso-occlusive crisis topic encompassed pain management, hydration, incentive spirometry, and target oxygen saturation levels. For acute chest syndrome, the focus areas included imaging techniques such as lung ultrasound, computed tomography scans, and echocardiography; treatment with systemic corticosteroids; non-invasive ventilation; prophylactic and therapeutic anticoagulation; and procalcitonin and antibiotic therapy. The section on transfusion therapy addressed indications and methods of transfusion, as well as the diagnosis and prediction of delayed hemolytic transfusion reactions. A total of 45 recommendations were proposed, including 14 specific to adults, 13 specific to pediatrics, and 18 applicable to both adults and children, along with three therapeutic algorithms. The Grade of Recommendation Assessment, Development, and Evaluation (GRADE) methodology was adhered to throughout the process. Sixteen recommendations were based on a low level of evidence (GRADE 2+ or 2−), while 26 were based on evidence that could not be classified under the GRADE system and were therefore considered expert opinions. Finally, for three aspects of sickle cell disease management, the experts concluded that no reliable recommendations could be made based on the current state of knowledge. The recommendations and therapeutic algorithms received strong agreement from the experts.